ICD-10 for the Dermatologist and Psoriasis Care Provider. Issue 4 (December 2014) - Algzlan, Haitham; Varada, Sowmya; Posnick, Mark; Gottlieb, Alice B.
On March 31, 2014, the U.S. Department of Health and Human Services announced an Oct. 1, 2015, deadline for the implementation of ICD-10. Importantly, the shift will be immediate, with no rollout or overlap period. This means that starting on Oct. 1, 2015, any claims filed using ICD-9 codes will be denied. This article hopes to provide an overview of ICD-10, the main differences between the 9th and 10th version, and its implications for the dermatology practice and those who manage psoriasis.